Between Capo S. Alessio and Capo Scaletta: urban surveys - Marinella Arena (Disegnare con, 2017)
This study started in 2012 with the relief of the village of Mandanici located on the Straits of Messina, on the slopes of the eastern Peloritani, now includes the reliefs of: Forza D’Agrò 2013; Alì 2014; Fiumedinisi 2015 and Itala 2017. The villages were analysed in their entirety by evaluating the correlations between architecture, urban space and landscape. The  research goals are many. The first is to test a survey protocol for a whole urban centre and provide complete documentation. The second concerns the analysis of these centres from a typological, formal, decorative and structural point of view. The third point is the definition of micro urban areas with specific risk factors related to soil morphology, abandonment of buildings, dimensional and structural typology of individual buildings. In the end, the goal is to transcend all research, to increase the awareness of the architectural and landscape  value of these places in the inhabitants, first custodians and keepers of these places, and in occasional users.